Antibacterial Activity of 4-hydroxychalcone Against Bacterial Contaminant of Packed Red Cells - Kusumaningrum, Serafica Btari Christiyani; Sepvianti, Wiwit; Pebrina, Relita; Rahman, Aulia (Indonesian Journal of Biology Education, 2022)
The bacterial contamination of blood products is still become a serious problem in consideration, thus it can cause the risk of blood transfusion, namely bacterial sepsis. Packed red cells is blood product and potentially contain bacterial contaminant. The source of bacterial contamination can come from the skin disinfection process in less aseptic during blood collection, donor bacterimia, and  blood processing. In response, currently there have been many antibacterial compounds developments purposely to reduce the risk of bacterial contamination of blood products. This study aimed to observe the activity of 4-hydroxychalconecompounds in contaminant bacteria isolated from packed red cells blood products. Bacterial isolates isolated from the packed red cells were Staphylococcus aureusbased on cell morphology, biochemistry and colony shape. The antibacterial activity of 4-hydroxychalchone compound against Staphylococcus aureus isolates used the diffusion method. The results showed, there were antibacterial activity of 4-hydroxychalchone at a concentration of 2.5% 1.25% and 0.625% against packed red cells contaminant bacteria based upon the clear zone formed. In conclusion, the bacteria isolate was obtained from the PRC was gram positive bacteria, Staphylococcus aureus. The 4-hydroxychalcone had successfully synthesized and has antibacterial activity against S. aureus isolated from PRC, with the biggest inhibition power was 71,36% at 5,0% of chalcone concentration.